2005
DOI: 10.1111/j.1349-7006.2005.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptosins isolated from marine fungus Leptoshaeria species inhibit DNA topoisomerases I and/or II and induce apoptosis by inactivation of Akt/protein kinase B

Abstract: (1-4) Class I enzymes (topo I, EC 5.99.1.2) act by making a transient break in one DNA strand, allowing the DNA to swivel and release torsional strain, changing the linking number by steps of one.(2,4) Class II enzymes (topo II, EC 5.99.1.3) make transient breaks in both strands of one DNA molecule, allowing the passage of another DNA duplex through the gap, changing the linking number by steps of two.(1-3) These enzymes are crucial for cellular genetic processes such as DNA replication, transcription, recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…It has been reported that CPT-11 can induce the caspase-3 activity through down-regulation of the phosphatidylinositol 3-kinase [PI(3)K]-Akt signal pathway, which leads induction of apoptotic cell death (15). In wild-type cells, the protein abundance of phosphorylated Akt (p-Akt) was obviously decreased by treatment of the cells with DEX or CPT-11 ( Fig.…”
Section: Dex Fails To Enhance the Cpt-11-induced Apoptotic Signaling mentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that CPT-11 can induce the caspase-3 activity through down-regulation of the phosphatidylinositol 3-kinase [PI(3)K]-Akt signal pathway, which leads induction of apoptotic cell death (15). In wild-type cells, the protein abundance of phosphorylated Akt (p-Akt) was obviously decreased by treatment of the cells with DEX or CPT-11 ( Fig.…”
Section: Dex Fails To Enhance the Cpt-11-induced Apoptotic Signaling mentioning
confidence: 97%
“…On the other hand, the cytotoxic effect of CPT-11 is also caused by the promotion of apoptotic cell death through down-regulation of the PI(3)K-Akt survival pathway (15). The serine / threonine kinase Akt is a downstream effector of PI(3)K that is recognized as the major mediator of survival signals that protect cells from undergoing apoptosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…), tafluposide (F 11782), a novel epipodophylloid, and XR11576, a novel phenazine. [46][47][48][49][50] …”
Section: Dual Topoisomerases I and Ii Inhibitorsmentioning
confidence: 99%
“…Dual monoamine oxidase B inhibitors and adenosine A2A receptor antagonists Methylxanthines [26] and (E,E)-8-(4-phenylbutadien-1-yl)caffeine [27] Inflammation Dual cyclooxygenases (COX-1 and COX-2) and 5-lipoxygenase (5-LOX) inhibitors Flavocoxid [28] and ML3000 (2,2-dimethyl-6-(4-chlorophenyl)-7-phenyl-2,3-dihydro-H-pyrrolizine-5-yl) acetic acid [29] Hypertension Dual inhibitors of neprilysin and angiotensin-converting enzyme BMS-182657, [30] MDL-100173 [31] and S21402 (RB105) {N-[2S,3R-(2-mercaptomethyl-1-oxo-3-phenylbutyl)-l-alanine]} [32] Dual inhibitors of the angiotensin II receptor and neprilysin LCZ696 [33] Dual inhibitors of angiotensin-converting and endothelin-converting enzymes CGS 26303 [34] and SLV 306 (Daglutril) [35] Dual vasopressin receptor (V1/V2) antagonists (RWJ-676070) [36] Thrombosis Dual-acting anticoagulant/antiplatelet inhibitors MC45301, MC45308, MC45350, and MC45403 derived from vitamin B6 (pyridoxine) [37] Microbial infections Dual inhibitors of type I and type II DNA topoisomerases Some novel indolyl quinoline analogs [38] Dual inhibitors of b-ketoacyl-[acyl carrier protein (ACP)] synthase II (FabF) and III (FabH) Platencin [39] Viral infections Dual inhibitors of human immunodeficiency virus type 1 (HIV-1) integrase and RNase H Madurahydroxylactone derivatives [40] Dual inhibitors of 2A and 3C proteases encoded by human rhinoviruses (HRVs) LY343814 [41] Cancer Dual PI3K and mTOR inhibitors PI-103, [42] NVP-BEZ235, [43] WJD008 [44] and BAG956 [45] Dual topoisomerases I and II inhibitors Benzophenanthridine alkaloids, indolocarbazoles and lipophilic bis(naphthalimides), anthraquinones, pyridoindoles, indenoquinolones, acridines, TAS-103, leptosins (Leps) F and C, tafluposide (F 11782) and XR11576 [46][47][48][49][50] Dual inhibitors of epidermal growth factor receptor, ErbB-2, and vascular endothelial growth factor receptor-2 NVP-AEE788 [51] Dual inhibitors of IkappaB kinase-2 (IKK2) and Fms-like tyrosine kinase 3 (FLT3) AS602868 [52] The new hybrids retain the potent and selective human AChEinhibitory activity of the parent 6-chlorotacrine, while exhibiting a significant in-vitr...…”
Section: Parkinsonismmentioning
confidence: 99%
“…As a result, leptosins C (258) and F (261) were found to be catalytic inhibitors of topo I and be able to inhibit the Akt pathway. Especially, 258 possesses the in vivo catalytic inhibition of topo I and can induce apoptosis in RPMI8402 cells by accumulation of cells in sub-G1 phase, activation of caspase-3, and degradation of chromosomal DNA (Yanagihara et al 2005). Additionally, leptosin M (271) showed appreciable inhibition of a panel of human cancer cell lines from breast, CNS, colon, lung, melanoma, ovary, kidney, stomach, and prostate with a mean GI 50 value of 5.62 μM (Yamada et al 2002).…”
Section: Peptidesmentioning
confidence: 99%